Synthesis of Renewable Poly(limonene): A Kinetic Modeling Study to Improve the Polymerization - Coelho,Felipe Mourão (2020)
Abstract Despite its potential in the production of polymers from renewable sources, D-limonene faces difficulties in its polymerization, resulting in low monomer conversion and molar mass. In order to investigate the non-ideality inherent kinetics, this work explores different modeling strategies for D-limonene radical polymerization, using benzoyl peroxide as initiator. The starting model considered the classical approach for conventional radical polymerization. This model was then corrected by including reaction orders different from the unit. After an analysis and choice of the best model, computer simulations were compared with experimental results from literature, validating the chosen approach. It was found that the process is drastically influenced by chain transfer reactions, presenting a non-ideal behavior. Finally, an analysis of distinct reaction conditions provided information on monomer conversion, molar mass and polymer dispersity, which could guide future research in the synthesis optimization. Higher molar mass poly(limonene) were obtained by simultaneously reducing the monomer and initiator concentrations.